Incidents in the Life of a Slave Girl, Written by Herself - Jacobs, Harriet A. (Harriet Ann), 1813-1897; Child, Lydia Maria, 1802-1880 (Salt Lake City, UT : Project Gutenberg, 2004)
"Incidents in the Life of a Slave Girl, Written by Herself" by Harriet A. Jacobs is an autobiography published in 1861. Written under the pseudonym Linda Brent, Jacobs recounts her experiences as an enslaved woman and mother who endured sexual abuse and years of hiding before escaping to freedom. She addresses Northern white women directly, revealing the particular horrors faced by enslaved mothers and challenging prevailing notions of womanhood that excluded Black women from their protection. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Incidents_in_the_Life_of_a_Slave_Girl
Release date is 2004-02-01
Juliet Sutherland, Andre Lapierre and PG Distributed Proofreaders. Revised by Richard Tonsing.
Keywords: Enslaved women -- United States -- Biography; Enslaved persons -- United States -- Biography; Enslaved persons -- United States -- Social conditions; Jacobs, Harriet A. (Harriet Ann), 1813-1897